Erosion under turbulent flow: a CFD-based simulation of near-wall turbulent impacts with experimental validation. Issue 1 (31st December 2022) - Espinoza-Jara, Ariel; Walczak, Magdalena; Molina, Nicolas; Jahn, Wolfram; Brevis, Wernher
Abstract : Engineering systems operating under particle-laden turbulent flow regimes, such as slurry pumps, are prone to erosive wear, where the specific conditions of particle impingement are crucial for determining the wear rate of the eroding surface and thus its relevance for the mechanical or hydraulic system. However, the near-wall interactions under turbulent flows impose a challenge for the formulation and validation of experimental and numerical models that describe the particle's trajectories close to the surface. This work analyzes the statistics of particle impacts obtained from a Large-Eddy Simulation (LES) with the Wall-Adapting Local Eddy-Viscosity (WALE) model of the flow and its consistency with experimental data on the statistical distributions of particle impact angle and impact direction determined in a slurry pot configuration. The resulting distributions of impact angle, impact direction, and particle velocity derived from the implemented CFD formulation produced characteristic values similar to those derived from experimental data. The LES-WALE approach used in this work offers shorter computational times and is shown valid by comparative analysis with direct simulation. The model's applicability and prospective dynamic simulation of practical engineering cases are discussed.